Platelets induce epithelial to mesenchymal transition in renal proximal tubular epithelial cells through TGF-β signaling pathway - Rustiasari, Ukhti Jamil; Uil, Melissa; Zhang, Xiaomeng; Claessen, Nike; Butter, Loes; Florquin, Sandrine; Tammaro, Alessandra; Roelofs, Joris J.T.H. (Molecular medicine (Cambridge, Mass.), 2025)
Background Management of chronic kidney disease (CKD) remains a major challenge due limited therapeutic options to reverse fibrosis, which is a critical feature in CKD. Partial epithelial-to-mesenchymal transition (EMT) of tubular epithelial cells (TECs) is a key driver of fibrosis, and has become an important focus for kidney protection strategies. Blood platelets, a major source of circulating transforming growth factor beta (TGF-β), are implicated in pathogenesis of CKD, but their involvement in EMT and kidney fibrosis remains uncertain. Methods We used two mouse models of renal fibrosis—diabetic kidney disease (DKD) and unilateral ureter obstruction (UUO)—to examine the connection between platelets, partial EMT, and fibrosis. Platelet inhibition or depletion was performed to assess EMT, cell cycle arrest, and fibrosis. In vitro, platelets were applied to TECs and kidney organoids. To determine the role of TGF-β signaling, we used TGF-βRI inhibitor. Expression of EMT, and fibrosis markers, as well as TGF-β1 signaling, were analyzed using western blot, reverse transcription quantitative PCR (RT-qPCR), enzyme-linked immunosorbent assay (ELISA), and immunostaining. Results In both animal models, platelet inhibition or depletion resulted in reduced expression of cell cycle arrest marker p21, partial EMT and fibrosis. In vitro, activated platelets stimulated cell cycle arrest, EMT, and fibrosis in TECs and kidney organoids. Chronically injured TECs experience cell-cycle arrest which promote a paracrine EMT program in TECs, jointly leading to fibrosis. This platelet-mediated effect on cell cycle arrest and EMT was driven by TGF-β1 signaling, as selective inhibition of the TGF-β receptor rescued these dysfunctional phenotypes. Conclusion Our study demonstrates that platelets activate the TGF-β1 pathway, leading to cell cycle arrest, EMT and renal fibrosis. These findings suggest that antiplatelet therapies may have potential renoprotective effects by protecting tubular homeostasis, attenuating partial EMT and fibrosis.